KEEFEKTIFAN PROGRAM PENDIDIKAN MASYARAKAT BERBASIS PEMBERDAYAAN PEREMPUAN MELALUI PEMBERIAN MODAL USAHA KURSUS MENJAHIT - Herlina, Herlina (Jurnal Paedagogy, 2020)
The empowerment program is a developing program because it has a positive impact on the community, namely the provision of skills among them is sewing skills, however sewing skills without being supported by the willingness of sufficient capital to support the skills that have been obtained will certainly not have any effect. The provision of capital by the central government and local governments greatly contributes to the smooth implementation of the program. The provision of capital plays a very important role in increasing the learning motivation of students to continue to be active in developing the potential of the students which also has an effect on the effectiveness of the program launched can be used as a measure of the success of an organized program, besides that there are also many other factors that affect the effectiveness of a program. This research was conducted at PKBM Hidayat Jati Bedusi in Ampenan, West Nusa Tenggara Province for 6 months. The research subjects consisted of PKBM managers, community leaders and several residents who were targeted by the women's empowerment program. The evaluation model used is the CIPP model from Stufflebeam which consists of context, input, process, and product. Based on the results of this study, the following results were obtained: In the context element Input, process and product based on the results of data analysis, it can be seen that the effectiveness of the program of providing business capital in PKBM Hidayat Jati Bedus, Dayan Peken Village, Ampenan District is quite effective, this can be seen from the results of the analysis All evaluation components are in the quite effective category which can be seen from the acquisition of an average score of 44.55.